BUILDING ART DIPLOMACY: THE CASE OF CONTEMPORARY AMERICAN ART EXHIBITION IN LATIN AMERICA, 1941 - Matallana, Andrea (ShodhKosh: Journal of Visual and Performing Arts, 2022)
This article analyzes the construction of the visual narrative expressed in the exhibition Contemporary North American Painting in 1941. During the II World War, the U.S. government recovered the initiative to build a strong tight with Latin American countries by relaunching the Good Neighbor Policy. Cultural diplomacy was an important branch of this policy. With the purpose of winning friends in the continent, the government created the Office of Inter-American Affairs, led by Nelson Rockefeller, and he sent artists, intellectuals, and exhibitions to make North America known in the other Americas. The Contemporary North American Painting projected an image of the United States as a modern and industrialized society to South Americans. This narrative was one of the devices developed by the U.S. government as part of the soft diplomacy carried out in the 1940s. In this article, we delve into the construction of the visual narrative about the U.S as part of the Good Neighbor exhibition complex, and we will analyze how the exhibition process was thought of as part of representational and ideological machinery. The article was based on reading, analysis, and cataloging of primary sources. The sources were letters, catalogs, photos, and notes from the main characters of the Office of Inter-American Affairs. Likewise, the exhibited works of art were operationalized.